(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
Volumetric and viscometric properties of cationic surfactant cetylpyridinium bromide in aqueous ascorbic acid solutions were studied. The apparent molar volumes, standard partial molar volumes in dilute solutions, transfer apparent molar volumes at infinite dilution and viscosity B-coefficients were determined. It was concluded that the behavior of volumetric and viscometric properties in studied ternary system is mainly determined by hydrophobic interactions.